Determination of contact stresses in the boundary area considering elastomere-pad bending as example - Geiger, Manfred; Merklein, Marion; Trägler, Horst; Nock, Marco (Production Engineering - Annals of the WGP, 2005)
LFT Import::2019-08-05 (1218)

Erfassung von Kontaktspannungen im Flansch während wirkmedienbasierter Blechumformprozesse - Merklein, Marion; Trägler, Horst; Blankl, Andreas (Automobiltechnik in Bayern, 2009)
LFT Import::2019-07-29 (1583)

Establishment of a new biomechanical measurement method for surface deformation of bone by force application via dental implants—a pilot study - Matta, Ragai; Riegger, Katharina; Trägler, Horst; Adler, Werner; Eitner, Stephan; Wichmann, Manfred; Motel, Constantin (Applied Sciences, 2021)
Purpose: To date, the qualitative and quantitative recording of biomechanical processes in dental implants represents one of the greatest challenges in modern dentistry. Modern, dynamic, 3D optical measurement techniques allow highly constant and highly accurate measurement of biomechanical processes and can be superior to conventional methods. This work serves to establish a new measurement method. Materials and Methods: A comparative analysis was undertaken for two different measurement systems, two conventional strain gauges versus the 3D optical two-camera measurement system ARAMIS (GOM GmbH, Braunschweig, Germany), as they detected surface changes on an artificial bone block under masticatory force application. Two implants (Straumann Standard Implants Regular Neck, Straumann GmbH, Freiburg, Germany) were placed in the bone block, and three different three-unit bridges were fabricated. Increasing masticatory forces, from 0 to 200 N, were applied to the bone block via each of these bridges and the inserted implants. Fifteen repetitions of the test were performed using a universal testing machine. The computer unit of the ARAMIS system was used to simultaneously integrate the surface changes recorded by the strain gauges and the ARAMIS system. The areas on the bone block examined by the dynamic 3D optical measurement method corresponded exactly to the locations and extent of the strain gauges. A statistical comparative analysis was carried out separately for the strain gauges and the corresponding optical measuring surface at the defined force magnitudes. The equivalence test and the intraclass correlation served as statistical means. Results: In the case of the intraclass correlation, a clear concordance of both measurement methods could be shown for all examined cases. For the equivalence test, no significance could be shown in individual cases. Conclusion: The accuracy of the modern, dynamic, 3D optical measurement method is comparable to that of conventional strain gauges. On this basis, versatile new research approaches in the field of biomechanics of dental implants can be pursued by establishing this method.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Bone deformation; Dental implants; Implant biomechanics; Strain

Es werde Strom - Dietrich, Simon; Trägler, Horst; Otto, Andreas (Design & Elektronik, 2007)
LFT Import::2019-07-16 (1398)